2017
DOI: 10.1111/anti.12351
|View full text |Cite
|
Sign up to set email alerts
|

Communal Performativity—A Seed for Change? The Solidarity of Thessaloniki's Social Movements in the Diverse Fights Against Neoliberalism

Abstract: The debate on the financial crisis is at an impasse. Neoliberal austerity discourse is often positioned as an almost insurmountable barrier, its disciplinary power affecting even the most change‐oriented citizen‐initiatives existing today. Countering this, this paper highlights the transformative capacity of social movements in Thessaloniki. Drawing from Butler, Laclau and Mouffe, and Gibson‐Graham we develop the notion of “communal performativity” both as an academic and as a practical concept to understand a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 47 publications
0
15
0
2
Order By: Relevance
“…Allen [25] (p.10) highlights how local food systems in the US continue to marginalise some social groups through pluralist democratic organising, because asymmetrical distributions of power are being upheld, "which amplify some voices or completely drown out others". Some research in Greece has also shown disagreement and division in solidarity initiatives (e.g., [6]). Rakopoulos' [26] raises sources of conflict in the Greek no middlemen initiatives, including tensions caused by institutionalization and its consequences for radical politics.…”
Section: The Meaning Of Solidarity (Economy)mentioning
confidence: 99%
See 4 more Smart Citations
“…Allen [25] (p.10) highlights how local food systems in the US continue to marginalise some social groups through pluralist democratic organising, because asymmetrical distributions of power are being upheld, "which amplify some voices or completely drown out others". Some research in Greece has also shown disagreement and division in solidarity initiatives (e.g., [6]). Rakopoulos' [26] raises sources of conflict in the Greek no middlemen initiatives, including tensions caused by institutionalization and its consequences for radical politics.…”
Section: The Meaning Of Solidarity (Economy)mentioning
confidence: 99%
“…There is also a growing fear of co-optation (a form of homogenisation) of social movement politics in solidarity economies, particularly pertinent given the spotlight on Greece as a centre point of radical solutions to crisis, which Rakopoulos [27] contends can give rise to romanticised accounts of solidarity economy. Steinfort [6] argues from a post-structuralist perspective that movements in Thessaloniki could avoid fragmentary strategizing based on identity politics by undertaking "communal performative" narratives as transformation strategies that respect antagonisms and differences. This article contends alternatively that conflict, and the belief that it is inevitable, is exaggerated by overlooking the importance of structural difference in defining dynamics of self-organised initiatives.…”
Section: The Meaning Of Solidarity (Economy)mentioning
confidence: 99%
See 3 more Smart Citations